Fecal metabarcoding vs traditional invasive survey to access the diversity of anuran endoparasites and diet - Amanda Dudczak; Rafael Euclydes; Emanuel Razzolini; Hernani Fernandes Magalhães de Oliveira; Melissa Ingala; Karla Magalhães Campião (Parasitology)
Identifying interactions between species is essential for understanding ecosystem dynamics. With their central position in trophic networks, anurans underscore the importance of studying their interactions with other organisms. Traditionally, collecting and describing anuran helminth parasites rely on lethal methods, posing challenges for studying threatened species. In this study, we tested the effectiveness of non-invasive fecal metabarcoding and compared its accuracy to traditional invasive methods for identifying parasites and dietary components. We collected anurans from 6 families in the Brazilian Atlantic Rainforest and analysed their feces using the 18S marker while performing necropsies for traditional identification. Traditional methods identified 12 parasite taxa and 3 dietary items at lower taxonomic resolution. Fecal metabarcoding, on the other hand, revealed greater diversity and fine taxonomic resolution for dietary items, although with lower accuracy for parasites due to database limitations. The metabarcoding approach demonstrated a high potential for non-lethal biodiversity assessments, offering a more comprehensive view of dietary diversity and a viable alternative for studying parasites in vulnerable populations. However, its effectiveness depends on improving reference databases, especially for parasite taxa. The advancement of non-invasive approaches that integrate parasitological data holds great potential to improve conservation strategies and enhance the ecological understanding of amphibian-parasite interactions.